Ekonomiska konsekvenser av förändrad röttolerans vid Bravikens Pappersbruk - Rajala, Fredrik (SLU/Dept. of Forest Products, 2006)
The competition for Norway spruce pulp wood in Central Sweden increases, forcing the supply-structure of Holmen to face two important challenges. Firstly, it is of the outmost strategically importance to secure the long-term supply of Norway spruce pulp wood to the industries. Secondly, Holmen desires to increase the obtainable volume of Norway spruce pulp wood. This would enable the company to choose volumes in the lower price-segments and thereby decrease the dependency of costly marginal volumes. As this work shows, one part in managing these challenges could be to lower the quality standards concerning root rot (Heterobasidium annosum).